Surface Functionalization of Graphene Oxide with Polymer Brushes for Improving Thermal Properties of the Polymer Matrix - Shuangshuang Wang; Houfang Chi; Lin Chen; Wei Li; Yuchao Li; Guang Li; Xiangcai Ge (Advances in Polymer Technology)
In this work, polymethyl methacrylate (PMMA) and polystyrene (PS) with controlled structures would be grafted on graphene material. The hybrid materials were prepared by coating graphene oxide (GO) with polydopamine (PDA) as a reactive underlayer and reducing agent, subsequently, surface-initiated polymerization of monomers (methyl methacrylate, styrene) based on the activators regenerated electron transfer atom transfer radical polymerization (ARGET-ATRP) technique. The polymer brush-modified graphene materials were then incorporated into the PMMA or PS matrix to get polymer nanocomposites with better thermal properties. The results of Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and thermal gravimetric analysis (TGA) demonstrated that PMMA and PS chains were successfully anchored on the surfaces of functionalized GO sheets. The influence of the grafted polymer brush-modified GO on thermal stability of PMMA and PS was investigated by a simultaneous thermal analyzer. Thermal conductivity of the polymer nanocomposite was determined by a conductive calorimeter. The results showed that thermal stability, glass transition temperature (Tg), and thermal conductivity of the polymer nanocomposites were obviously improved compared with pure PMMA or PS.